Centrifugation-induced assembly of dense hotspots based SERS substrate for enhanced Raman scattering and quenched fluorescence. (4th June 2022) - Su, Dan; Zhang, Xiao-Yang; Chen, Xia-Yao; Wang, Shan-Jiang; Wan, Qing-Dian; Zhang, Tong
Abstract: Hanging (aggregation stuck to the centrifugal tube) in the centrifugation process is always regarded as an unwanted condition. In this work, we develop a centrifugation-induced assembly of dense hotspots surface-enhanced Raman scattering (SERS) substrates from the hanging phenomenon. We discovered interesting sintering-resistant behavior (maintain the sharp nanotip features) of star-like Au nanoparticles after centrifugation-induced assembly, which is in stark contrast with the sintering phenomenon of sphere-like nanoparticles. We also found that one side of centrifugal-induced Au assemblies is two-dimensional (2D, root mean square (rms) roughness down to ∼10 nm), while the other is three-dimensional (3D, rms roughness more than 100 nm). The close-packed feature of the Au assemblies makes them candidates as dense hotspots based SERS substrates. Through systematic investigation of SERS performance of centrifugation-induced assemblies with different morphology (star-like and sphere-like, 2D and 3D), it was found that the 3D side of star-like Au nanoparticles assembly exhibits the highest SERS enhancement together with quenched fluorescence. The star-like SERS substrate also displays high detection uniformity (with 10 −7 M Rhodamine 6G) and a low detection limit (down to 10 −12 M Rhodamine 6G).